MICRO-HARDNESS OF RAPIDLY QUENCHED OF SOME ALUMINIUM ALLOYS (AL 14-16% CU AND AL 4% CU) - Ghatus, M.; Ghamate, R.; Essari, A. (Conference On Engineering Science and Technology, 2021)
Two simple apparatus based on the hammer and anvil principle have been constructed and used to study the micro-hardness of some AL-base alloys. Foils with thicknesses arranging from 20 µm up to 600 µm have been obtained. The cooling rate was estimated to be in the range of 1.6x104:7.5x104 k sec-1.Rapid quenching of Al- 14-16% Cu showed the micro-hardness increases particularly in foils below 0.3 mm in thickness. Isochronal annealing of theses foils show that the highly supersaturated Al-14-16% Cu solid solution decomposes readily at relatively low temperature and short time intervals. The maximum hardness is obtained after annealing at 100 C for 30 minutes. However, with decreasing the Cu content of the foils the precipitation process is largely delayed. Eight hours of annealing at 100 ºC was not enough to achieve the maximum hardness in Al-4% Cu thin foils. The achieved hardness value was more than twice of the maximum hardness obtained in articles of similar composition but conventionally aged.
Keywords: Aluminium; Copper; Isochronal; Micro-hardness; Rapid quenching